2023
DOI: 10.1155/2023/3528977
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Fiber-/Nanofiller-Based Polymer Composites in Mechanical and Erosion Performance: A Review

Abstract: The addition of nanofillers in the polymer matrix composites (PMC) has shown a considerable improvement in the mechanical properties and acts as a suitable replacement material. Among the various properties, erosion studies play a key role in the establishment of new materials in engineering applications irrespective of material properties. This paper primarily focus on mechanical properties of PMC and provides a view of the erosion studies conducted on various PMC that are reinforced with natural fibers and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 132 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Potluri et al [16] studied the influence of architectural topology on the impact damage of 3D woven composites and reported that the ability to withstand damage depended on the weave topology geometry of individual tows. Also, 3D woven textiles showed significant damage resistance when compared with 2D laminated composites [17]. Textile composites could benefit from rate-dependent deformation through the large angular rotation between warp and weft yarns; hence, their deformation was dominated by shear behaviour [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potluri et al [16] studied the influence of architectural topology on the impact damage of 3D woven composites and reported that the ability to withstand damage depended on the weave topology geometry of individual tows. Also, 3D woven textiles showed significant damage resistance when compared with 2D laminated composites [17]. Textile composites could benefit from rate-dependent deformation through the large angular rotation between warp and weft yarns; hence, their deformation was dominated by shear behaviour [18].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are a number of published data on such rate-dependent solid-particle erosion of these advanced textile composites [15][16][17][18][19][20][21][22][23]. Some early studies [20][21][22][23] showed that the fibre structures might influence erosive characteristics of the composites and the erosion could lie in a transition zone between brittle and ductile material behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing Nano fillers offers the advantage of needing fewer fillers to achieve specific multifunctional properties, compared to traditional microscale fillers. Combining GFRP composites with Nano fillers significantly enhances their performance, particularly in structural applications [1]. Different production parameter combinations yield distinct optimal outcomes.…”
Section: Introductionmentioning
confidence: 99%